Age, weight and decompression sickness in rats. (14th March 2016) - Buzzacott, Peter; Theron, Michael; Mazur, Aleksandra; Wang, Qiong; Lambrechts, Kate; Eftedal, Ingrid; Ardestani, Simin Berenji; Guerrero, François
Abstract: Objective : The aim of this study was to determine if, after controlling for weight, age is associated with decompression sickness (DCS) in rats. Methods : Following compression-decompression, male rats aged 11 weeks were observed for DCS. After two weeks recovery, surviving rats were re-dived using the same compression-decompression profile. Results : In this experiment, there was a clear difference between DCS outcome at ages 11 or 13 weeks in matched rats ( p  = 0.002). Discussion : Even with weight included in the model, age was significantly associated with DCS ( p  = 0.01), yet after removal of weight the association was much stronger ( p  = 0.002). Conclusion : We believe that age is likely to be found associated with the probability of DCS in a larger dataset with a wider range of parameters, after accounting for the effect of weight.